2018
DOI: 10.1093/jat/bky018
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Eight QT-Prolonging Drugs and Their Main Metabolites Between Postmortem Cardiac Tissue and Blood Reveals Potential Pitfalls in Toxicological Interpretation

Abstract: Femoral blood concentrations are usually used in postmortem toxicology to assess possible toxic effects of drugs. This includes QT-prolongation and other cardiac dysrhythmia, which could have been the cause of death. However, blood concentration is only a surrogate for the active site concentration, and therefore cardiac tissue concentration may provide a more accurate toxicological interpretation. Thus, cardiac tissue and femoral and cardiac blood concentrations were examined for eight frequently used QT-prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Published values of the maxium concentration for methadone in patients undergoing opioid replacement therapy are 5‐ to 10‐fold lower than the IC 50 for suppression of I K1 and I Kr as reported here; however, cardiac tissue levels of methadone may be significantly higher than measured blood levels. 30 Indeed, we observed QT prolongation in patients following methadone induction, indicative of significant suppression of I Kr , and likely I K1 as well. However, we observed no cardiac arrhythmias or arrest in patients involved in the study.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Published values of the maxium concentration for methadone in patients undergoing opioid replacement therapy are 5‐ to 10‐fold lower than the IC 50 for suppression of I K1 and I Kr as reported here; however, cardiac tissue levels of methadone may be significantly higher than measured blood levels. 30 Indeed, we observed QT prolongation in patients following methadone induction, indicative of significant suppression of I Kr , and likely I K1 as well. However, we observed no cardiac arrhythmias or arrest in patients involved in the study.…”
Section: Discussionmentioning
confidence: 59%
“…Serum values may be unreliable indicators of myocyte receptor interactions, however. Directly measured cardiac concentrations of methadone averaged 4.7‐fold higher than serum concentrations at autopsy, 30 and therefore appear comparable to the IC 50 for suppression of I K1 . These data suggest that ordinary use of methadone will often result in substantial inhibition of I K1 .…”
Section: Discussionmentioning
confidence: 63%
“…This indicates that if the concentration in blood increases, the concentration in the alternative matrix also increases. Opioids are some of the most studied analytes in paired samples of peripheral blood and alternative matrices in the literature, where their concentration ratios in brain tissue, 21,27,32,35,[39][40][41] cardiac blood, [8][9][10]12,16,[40][41][42][43] and muscle tissue relative to peripheral blood 10,23,[40][41][42][44][45][46] are either reported or can be calculated from the concentrations. Even though some of the studies include many cases, there is a lack of consensus in the concentration ratios reported, with wide ranges generally being observed and the mean and median differing between studies.…”
Section: Opioidsmentioning
confidence: 99%
“…The affinity of psychotropic drugs towards cardiac ion channels is lower than their affinity towards their primary pharmacological targets such as the dopamine D 2 - or the serotonin 5-HT 2A- receptor and the K d of ion channel inhibition is above the therapeutic range ( Abi-Gerges et al, 2011 ; Hiemke et al, 2018 ; Silvestre et al, 2014 ). Nevertheless, due to accumulation of drugs in cardiac tissues leading to locally toxic concentrations or accidental intoxication, QT prolongation is feasible even under therapeutic drug concentrations ( Mikkelsen et al, 2018 ). However, clinical studies on this topic showed inconsistent results.…”
Section: Introductionmentioning
confidence: 99%